Comparison of Extraction Methods on Medicinal Plants from the Lauraceae, Myristicaceae, Myrtaceace, Piperaceace, Rubiaceace, Solanaceace, and Zingiberaceae Families - Susanti, Julia; Fitri, Widya; Thaib, Cut Masyitah; Napitupulu, Muhammad Irianto; Pebriyandi, Fajar; Marbun, Eva Diansari (CV. Nusantara Scientific Medical, 2025)
Indonesia is recognized as the second most biodiverse country in the world after Brazil. The use of medicinal plants in traditional medicine is gaining popularity due to their proven health benefits and fewer side effects compared to synthetic drugs. Several plant families, such as Myrtaceae, Rubiaceae, and Solanaceae, are known to include species widely utilized in traditional therapies. This study aims to compare the extract yields obtained through maceration, percolation, and Soxhlet extraction methods from various medicinal plants. The extraction process used 96% ethanol as a solvent. The results revealed that extract yields varied significantly depending on the extraction method applied. In conclusion, this study demonstrates that the choice of extraction method—maceration, percolation, or Soxhlet—significantly influences the extract yield obtained from different plant families.